166k views
4 votes
2 - (3x – 4) = 2x – 9​

User JnBrymn
by
5.9k points

1 Answer

5 votes

Answer:

2 - (3x – 4) = 2x – 9​

Explanation:

Step 1: Simplify both sides of the equation.

2−(3x−4)=2x−9

2+−1(3x−4)=2x−9(Distribute the Negative Sign)

2+−1(3x)+(−1)(−4)=2x−9

2+−3x+4=2x−9

2+−3x+4=2x+−9

(−3x)+(2+4)=2x−9(Combine Like Terms)

−3x+6=2x−9

−3x+6=2x−9

Step 2: Subtract 2x from both sides.

−3x+6−2x=2x−9−2x

−5x+6=−9

Step 3: Subtract 6 from both sides.

−5x+6−6=−9−6

−5x=−15

Step 4: Divide both sides by -5.

−5x

−5

= −15

−5

x=3

User Nagarajan S R
by
7.3k points